Diálogos com o Oriente: psicanálise e Zen, dois métodos para além do sentido - a dimensão do ato - Moutinho, Luciana (2015)
We can find in the work of Jacques Lacan several references to Zen Buddhism, which are, however, little explored by researchers in Psychoanalysis. Considering such references relate to important elements of Lacanian theory, we seek to locate them in Lacan's texts, specifically in his seminars and writings. At the same time, we also seek to understand historically the emergence of Zen Buddhism in the East and which were its main philosophical and methodological principles, searching in anthropologists texts, in texts of other scholars of the East as well as in texts by Zen Buddhist authors. This made it possible to identify the possible similarities and differences between Lacanian psychoanalysis and Zen Buddhism. The elements that stood out in this study were those concerned with the method of the Lacanian clinical analyst and the Zen master method. Thus, we see the similarities between the transmission method of Lacanian Psychoanalysis and the method used by Buddhist Zen masters in their transmission. Both cherish for a language that breaks the Aristotelian logic, both stand as non-dualistic (but with their respective specificities) and both cherish for an emptying of the "I" (also with their respective specificities). We also observed differences between both methods, such as the specificity of the analytical Act regarding to Nirvana as an "end" that Zen Buddhism aims. Zen, as a school of Buddhism, would propose to its practitioner reach a state of "no longer desire" or "do not give in to his/her desire"; while in psychoanalysis is understood that "not to want" is not possible for it being a constituent factor of the subject as a missing being , and therefore the end of the analysis is given by the accountability and the empowerment of the subject facing a jouissance wich he was subjected to. The specificity of the analytical act stipulates that the subject remains barred, divided, not being refunded the small object "a", and not being taken as part of a whole or a not barred big Other (A). The pass, or act of completion of an analysis, has as specific feature being what qualifies the analysand to occupy the analyst place